Type Selection and Fatigue Analysis of the Lifting Mechanism used in the Embedded Type Stereo Carport - Wang Chunhua; Wang Tangmin (Jixie chuandong)
The chain used in embedded type stereo carport sustain the main weight during the process of lifting stereo carport. The chain plate is the main part of the chain,and lifting the carport repeatedly leads to fatigue failure. The traction mode of 28 A and 20 A,two types of the single and double row of chain are chosen,the chain plate model is established by using the ANSYS software,the force analysis is carried out and the fatigue analysis is carried out through the finite element software Workbench. By comparing the two kinds of force distribution regularity of the chain plate,the optimal chain mode is selected. And the more about life and fatigue failure about the chain can be known,which is convenient for maintenance and replacement of chain in timely.